Fungal Diversity and Interactions in the Nasal and Oral Cavities of Individuals with Allergic Rhinitis, Asthma and Healthy Controls - Marcos Pérez-Losada (Microorganisms, 2025)
Allergic rhinitis and asthma are common chronic airway diseases that present significant public health challenges. Previous research has shown how the nasal and oral mycobiomes influence the onset, progression and severity of these two conditions, but no study so far has directly compared those mycobiomes within the same cohort during health and disease. To address this gap, I analyzed next-generation fungal ITS sequence data from 349 participants, including individuals with allergic rhinitis, asthma, and healthy controls. The nasal and oral mycobiomes showed a great overlap in composition but differed significantly (p < 0.04) in the relative abundance of several dominant genera. Moreover, only 18.6% of the fungal amplicon variants were shared among cavities. Microbial alpha-diversity was significantly higher (p < 0.05) in the nasal cavity, while beta-diversity varied significantly (p < 0.045) across all indices and clinical groups. Fungal networks were largely fragmented and showed relatively low ecological niche specialization, which contrasts with a previous study of bacteriomes from the same cohort. These networks also differed in structure, complexity and keystone nodes across clinical phenotypes. Overall, these findings highlight that the nasal and oral mycobiomes play distinct yet interconnected roles in allergic rhinitis and asthma.